Trade : The Missing Link to Opportunity - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, argued that the Doha Round presents an opportunity to rewrite the rules of an unfair trading system that holds back the potential of the poorest people. As important as aid is, as important as debt relief is, the opportunities generated by trade are far more significant. Unless the people of Africa and other poor countries have access to markets to sell their products, they will not escape poverty or be able to give their children a better future. He said, under the current rules, rich countries are allowed to keep barriers highest on the goods produced by poor countries. Wolfowitz emphasized that rich countries pay out a total of 280 billion dollars in subsidies to their farmers each year. But the real damage is done to farmers in poor countries who are denied markets to sell their goods. It is their children who go hungry, who are deprived of clean water, medicines, and the most basic necessities of life.